Contribution à l’étude du complexe Ascochyta sur pois (Pisum sativum L.) dans le Nord Ouest Algérien · Confrontation in vitro des souches vis-à-vis de quelques fongicides. · Test d’agressivité des souches pathogènes sur feuilles détachées. - GUEDIDER Hocine (My University, 2012)
Work presented is a contribution to the study of the complex Ascochyta sp agent responsible for the anthracnose of pea. Sixteen stocks of Ascochyta sp collected of two areas of the Algerian West (Mostaganem and Mascara), used in this study, and are characterized on the morphological and farming level. The action of certain systemic fungicides (Hexaconazole, Penconazole and Difénoconazole) and sulfur (Fungicidal of origin mineral) are also study in order to evaluate the mycelial growth rate and the capacity fongistatic on the germination of the spores of Ascochyta sp. A test of aggressiveness of the stocks of Ascochyta sp on detached pea leaves (Merveille of kelvedon Variety) is also carried. The results obtained show that the difénoconazole with various concentrations causes a total inhibition on the whole of the stocks of Ascochyta sp tested. On the other hand with the hexaconazole and the penconazole with weak concentration, one observes a light mycelial growth. The action of micronized sulfur is noticed by a total inhibition of the germination of the spores with 0.5g/l; with low concentration, a light rate of germination of the spores is noted for certain isolates. The results of the test on the aggressiveness of the stocks of Ascochyta sp on detached leaves of the pea Merveille of kelvedon variety, watch the existence of variability enters the stocks of Ascochyta sp.We notes the existence of four levels of aggressiveness, of the stocks highly aggressive, aggressive, fairly aggressive and no aggressive.
Keywords: Pisum sativum L., Ascochyta sp, mycelial growth, germination of the spores, Fungicides, Aggressiveness